The influence of trade contacts on grave equipment of Gniew community in the 14th-18th century - Grupa, Małgorzata; Krajewska, Magdalena; Majorek, Magdalena; Kozłowski, Tomasz (Geology, Geophysics and Environment, 2013)
Richness and variety of grave equipment (silk textiles, scapulars, crosses, rosaries and the other objects), revealed during archaeological exploration carried out in St. Nicolas church in Gniew and in the area of the former graveyard, confirmed trade contacts of local community with Western Europe and Asia. Grave finds (wreaths, various flowers) as well as silk garments give evidence that the town and the area dwellers belonged to wealthy social classes. Close relations with many trade centers and luxurious items imported from them had an apparent influence on preserving rich and ceremonial burial rites against obligatory sumptuary law forbidding splendor. Moreover, these multi-direction trade and social contacts had also an impact on spreading out pathogenic microorganisms and transmissive diseases, syphilis, among the others.